SDGs Strategies in Greek Hospitality SMEs: Overcoming Barriers to Sustainability Implementations - Agkoli , Panayiota (HAPSc Policy Briefs Series, 2024)
Sustainability has become a cornerstone for resilient and competitive business practices, especially within the tourism and hospitality industry. This paper examines the adoption of Sustainable Strategies among Small and Medium-sized Enterprises (SMEs) in the Greek Hospitality Sector. Drawing on research findings, the study identifies motivations, critical barriers such as high investment costs, insufficient government support, and a lack of understanding about sustainability certifications. Despite these challenges, the findings reveal that sustainability initiatives, including energy conservation and local sourcing, positively impact profitability. To address the gaps, this paper recommends targeted financial incentives, region-specific training programs, and the establishment of sustainability networks to foster collaboration. These measures aim to empower SMEs to integrate advanced sustainability practices, ensuring long-term benefits for businesses and the environment.